Laparoscopic resection of prenatally detected intra-abdominal testicular teratoma: Report of a neonatal case - Keigo Yada; Hiroki Ishibashi; Hiroki Mori; Mitsuo Shimada (Elsevier, 2017)
Prenatal detection of intra-abdominal testicular tumor is rare. In this paper, we discuss the early laparoscopic resection of prenatally detected testicular tumor of a neonate. At 33 weeks gestation, follow-up ultrasound showed the mass measuring 3 × 2 cm, on the fetal right lower quadrant. After full-term birth, we performed laparoscopic resection of the tumor, on day 14 of life. Histology of 4-cm right testicular tumor revealed immature teratoma. Postoperative course was favorable and no recurrence has occurred 3 years after operation. Prenatal diagnosis of the intra-abdominal testicular teratoma enabled the early tumor resection, and laparoscopic resection of the tumor is safe and feasible, even in a neonate.